Phytochemical Screening and Antioxidant Activities of Some Seaweed from Kabung Island Waters West Kalimantan - Desriani Lestari; Rafdinal Rafdinal (Jurnal Biologi Tropis, 2023)
Seaweed is one of the prima donna marine biota which is widely used as a natural antioxidant. Various species of seaweed are found growing naturally in the waters of Kabung Island, West Kalimantan. This study aims to determine the phytochemical content and antioxidant activity of each genus Turbinaria, Hypnea and Caulerpa from those collected in the waters of Kabung Island. Seaweed extraction uses maceration method with methanol to remove active compounds. Next, a phytochemical screening was performed using specific reagents such as alkaloids, steroids, flavonoids, tannins and saponins which will change color or form precipitates. The free radical scavenging method of 2,2-diphenyl-1-picrylhydrazyl (DPPH) solution was used to test the antioxidant activity of each seaweed extract. The active compound in the sample extract will be formed if there is a change in the color of free radicals from dark purple to light yellow or clean. The results showed that the phytochemical screening of the three seaweed extracts contained tannins, flavonoids and saponins. Meanwhile, positive alkaloids were found in Turbinaria and Caulerpa extracts, and steroids were indicated by the genus Hypnea and Caulerpa. Antioxidant screening showed that Caulerpa extract was categorized as a potent antioxidant with an IC50 value of 88.57 ppm, higher than the IC50 of Turbinaria and Hypnea extracts, which were 114.32 and 138.42 ppm respectively and classified as weak antioxidants.